Indonesia’s Economic Diplomacy at the G20 Summit - Primawanti, Henike; Khairunisa, Yasmin; Khalida, Nur; Daffa, Ismail (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This article aims to analyze Indonesia’s economic diplomacy in efforts to recover the economic sector after the Covid-19 pandemic at the 2022 G20 Summit. Researchers use qualitative methods by collecting data through literature studies, documentation studies, and internet searches. The results of this study indicate that Indonesia is utilizing the momentum of the G20 presidency through its diplomatic efforts to jointly improve global economic conditions as a result of economic, political turmoil and the spread of Covid-19. This paper also shows that Indonesia’s economic diplomacy is directed at efforts to transform the digital economy by paying attention to the Micro, Small and Medium Enterprises sector. It is expected that through this article academics who concerned about economic issues can seek for reference and for stakeholders to formulate policies related to post-covid-19 economic recovery.